LITERATUR REVIEW : HUBUNGAN SELF-EFFICACY DAN MINAT BELAJAR DALAM MENYELESAIKAN MASALAH MATEMATIS SISWA - Rika, Rika; Aisyah Nursyam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The ability to solve mathematical problems is an essential aspect of mathematics learning, influenced by affective factors such as self-efficacy and learning interest. This study aims to analyze the relationship between self-efficacy and learning interest in supporting students’ ability to solve mathematical problems. The method used is a systematic literature review of scientific articles published between 2022 and 2025, with searches conducted through Google Scholar, and SINTA using the keywords “self-efficacy,” “learning interest,” and “mathematical problem solving.” A review of 30 relevant articles shows that self-efficacy affects students’ confidence and perseverance, while learning interest enhances motivation and active engagement in the problem-solving process. Overall, both factors contribute positively to improving students’ mathematical problem-solving abilities.